Temperature And Humidity Optimization To Add Save Life Strawberry (Fragaria chiloensis, L.) - Kartika (International Journal of Science and Environment (IJSE), 2022)
This study aims to determine the appropriate temperature and humidity in the storage of strawberries, this research was carried out using 3 humidity treatments and 3 temperatures, namely humidity 65%, 75%, and 85% with a temperature of 10 oC, 15 oC, and room temperature, fruit fruit stored at room temperature lasts up to 3 days, while at 10 oC the fruit with 65% humidity treatment lasts up to 6 days, with 75% humidity for 6 days and with 85 % humidity it lasts for 7 days, at 15 oC the fruit with 65% humidity treatment lasts 5 days, with 75% humidity for 5 days and with 85% humidity lasts for 6 days, so based on research that has been done it is known that 85% humidity treatment with a temperature of 10 oC is the right storage for strawberries. The longest shelf life of strawberries is with a humidity treatment of 85% which is stored at 10 oC, which can extend the shelf life of 4 days longer when compared to storage at room temperature.